Neonatal outcomes according to different therapies for gestational diabetes mellitus - Amanda L. da Silva; Augusto R. do Amaral; Daniela S. de Oliveira; Lisiane Martins; Mariana R. e Silva; Jean Carl Silva (Brazilian Society of Pediatrics, 2017)
Objectives: To compare different neonatal outcomes according to the different types of treatments used in the management of gestational diabetes mellitus. Methods: This was a retrospective cohort study. The study population comprised pregnant women with gestational diabetes treated at a public maternity hospital from July 2010 to August 2014. The study included women aged at least 18 years, with a singleton pregnancy, who met the criteria for gestational diabetes mellitus. Blood glucose levels, fetal abdominal circumference, body mass index and gestational age were considered for treatment decision‐making. The evaluated neonatal outcomes were: type of delivery, prematurity, weight in relation to gestational age, Apgar at 1 and 5 min, and need for intensive care unit admission. Results: The sample consisted of 705 pregnant women. The neonatal outcomes were analyzed based on the treatment received. Women treated with metformin were less likely to have children who were small for gestational age (95% CI: 0.09-0.66) and more likely to have a newborn adequate for gestational age (95% CI: 1.12-3.94). Those women treated with insulin had a lower chance of having a preterm child (95% CI: 0.02-0.78). The combined treatment with insulin and metformin resulted in higher chance for a neonate to be born large for gestational age (95% CI: 1.14-11.15) and lower chance to be born preterm (95% CI: 0.01-0.71). The type of treatment did not affect the mode of delivery, Apgar score, and intensive care unit admission. Conclusions: The pediatrician in the delivery room can expect different outcomes for diabetic mothers based on the treatment received.